Isotope Enhanced Approaches in Metabolomics - Gowda, G. A. Nagana (Adv Exp Med Biol, 2012)
The rapidly growing area of “metabolomics,” in which a large number of metabolites from body fluids, cells or tissue are detected quantitatively, in a single step, promises immense potential for a number of disciplines including early disease diagnosis, therapy monitoring, systems biology, drug discovery and nutritional science. Because of its ability detect a large number of metabolites in intact biological samples reproducibly and quantitatively, nuclear magnetic resonance (NMR) spectroscopy has emerged as one of the most powerful analytical techniques in metabolomics. NMR spectroscopy of biological samples with isotope labeling of metabolites using nuclei such as (2)H, (13)C, (15)N and (31)P, either in vivo or ex vivo, has dramatically improved our ability to identify low concentrated metabolites and trace important metabolic pathways. Considering the somewhat limited sensitivity of NMR and high complexity of the spectra of biological samples, increased sensitivity and selectivity achieved through isotope labeling methods pave novel avenues to unravel biological complexity and understand cellular functions in health and various disease conditions. This chapter describes the current developments in isotope labeling of metabolites in vivo as well as ex vivo, and their potential metabolomics applications.